Estudo da apoptose na amebíase hepática experimental induzida pela Entamoeba histolytica e Entamoeba dispar. - Luciana Fernandes do Prado (2022)
Amebiasis is a disease that affects about 12% of the world's population, with Entamoeba histolytica responsible for lysing and penetrating the host's tissues and Entamoeba dispar representing asymptomatic cases. However, studies have demonstrated the ability of E. dispar to produce lesions in experimental models. The success of amoebic invasion in the host is due to tissue destruction by its virulence factors, capable of causing necrosis and apoptosis. There are few studies on apoptosis induced by E. Histolytica and E. dispar. Therefore, the objective of this study was to evaluate apoptosis in an experimental model of amoebic liver abscess (ALA) induced by E. histolytica and E. dispar, using the TUNEL assay (Terminal deoxynucleotidyl transferase dUTP nick-end labeling) and immunological reactions -histochemistry for Caspase 3, Bax and Bcl-2 markers. In all ALA's induced by E. histolytica (EH group) and E. dispar (ED group) TUNEL+ reactions were detected in cells with morphological aspects indicative of apoptosis, both of the host and the parasite. All ALA's also showed positive reactions for the three immunohistochemical markers analyzed. Unlike what was seen in the EH group, the morphometric analysis showed a smaller Caspase 3+ and Bax+ cleaved area, as well as a larger BCl2+ area in the ALA of the ED group, indicating lower levels of apoptosis in the ALA induced by this species. E. dispar and E. histolytica showed caspase 3 and Bax-dependent apoptosis, being more intense in the ED group, proving the lower ability of this species to survive in the ALA. Therefore, this study demonstrated for the first time that apoptosis is also present, and significantly so, in AHA experimentally induced by E. dispar. Also, the significant expression of cleaved caspase 3 in AHA suggested the involvement of the intrinsic pathway of apoptosis, and the expression of Bax and Bcl-2 demonstrated the importance of these two proteins in the modulation of apoptosis in both species.